2016
DOI: 10.1016/j.foreco.2015.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Eucalyptus grandis and Acacia mangium leaves and fine roots in tropical conditions did not meet the Home Field Advantage hypothesis

Abstract: a b s t r a c tUnlike Eucalyptus monocultures, nitrogen fixing trees are likely to improve the soil nutrient status through the decomposition of N-enriched litter. The Home Field Advantage (HFA) hypothesis states that plants can create conditions that increase the decomposition rates of their own litter. However, there may not be any HFA when most of the decomposers are generalists. A reciprocal transplant decomposition experiment of fine roots and leaves of Acacia mangium and Eucalyptus grandis was undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 77 publications
(108 reference statements)
5
38
0
6
Order By: Relevance
“…In general, increasing proportions of forest residue relatively rich in easily accessible C compounds (nonstructural carbohydrates, phenolics – energy‐rich C compounds) and relatively poor in recalcitrant C (condensed tannins, lignin, polyphenols) present the best correlation with litter mass loss (Northup et al ., ; Hättenschwiler & Jørgensen, ; Bachega et al ., ). The decomposition decay rate, k, of the forest residue fractions followed the order: leaves > bark > branches.…”
Section: Discussionmentioning
confidence: 97%
“…In general, increasing proportions of forest residue relatively rich in easily accessible C compounds (nonstructural carbohydrates, phenolics – energy‐rich C compounds) and relatively poor in recalcitrant C (condensed tannins, lignin, polyphenols) present the best correlation with litter mass loss (Northup et al ., ; Hättenschwiler & Jørgensen, ; Bachega et al ., ). The decomposition decay rate, k, of the forest residue fractions followed the order: leaves > bark > branches.…”
Section: Discussionmentioning
confidence: 97%
“…Such a phenomenon has been found when examining the interaction between climate and microbial communities , Averill et al 2016. Although HFA has been observed across a variety of different soil decomposer communities (Ayres et al 2009), it has been found absent in others (St John et al 2011, Bachega et al 2016. One explanation for this divergence is HFA only accounts for adaptation to a particular organic matter resource and does not account for the fact that some decomposer microbial communities simply decompose an array of necromass types more rapidly due to greater functional breadth (Keiser et al 2014).…”
Section: Microbial Communities Of the Necrobiomementioning
confidence: 92%
“…, Bachega et al. ). One explanation for this divergence is HFA only accounts for adaptation to a particular organic matter resource and does not account for the fact that some decomposer microbial communities simply decompose an array of necromass types more rapidly due to greater functional breadth (Keiser et al.…”
Section: The Necrobiomementioning
confidence: 98%
“…The percentage of remaining biomass in the litter bags still not decomposed was similar to that found in an E. urophylla plantation in the state of Bahia, in which Pinto et al (2016) verified rates of 73.56% at 180 days after the beginning of the experiment. In the state of São Paulo, Bachega et al (2016) at 180 days after experiment initiation, it was 63.00% of the leaf biomass remaining in the litter bags in an E. grandis planting. This pattern of recalcitrance seems to be characteristic of eucalypt leaves and may be mainly due to the high levels of lignin and polyphenols present.…”
Section: Leaf Decompositionmentioning
confidence: 99%